2019
DOI: 10.1111/ele.13288
|View full text |Cite|
|
Sign up to set email alerts
|

The mesoscavenger release hypothesis and implications for ecosystem and human well‐being

Abstract: Many apex scavenger species, including nearly all obligate scavengers, are in a state of rapid decline and there is growing evidence these declines can drastically alter ecological food webs. Our understanding of how apex scavengers regulate populations of mesoscavengers, those less‐efficient scavengers occupying mid‐trophic levels, is improving; yet, there has been no comprehensive evaluation of the evidence around the competitive release of these species by the loss of apex scavengers. Here we present curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…For some facultative scavengers, carrion is a resource consumed primarily when other food is scarce, which may further influence seasonal dynamics of road kill scavenging (Hill et al 2018a). When vulture (families Accipitridae and Cathartidae) populations decline, carrion can become increasingly available to mammalian scavengers (O'Bryan et al 2019), which has the potential to increase mammal consumption of road kill.…”
Section: Resultsmentioning
confidence: 99%
“…For some facultative scavengers, carrion is a resource consumed primarily when other food is scarce, which may further influence seasonal dynamics of road kill scavenging (Hill et al 2018a). When vulture (families Accipitridae and Cathartidae) populations decline, carrion can become increasingly available to mammalian scavengers (O'Bryan et al 2019), which has the potential to increase mammal consumption of road kill.…”
Section: Resultsmentioning
confidence: 99%
“…Increased scavenging opportunities opened by the loss of apex predators may lead to an increased abundance of the surviving scavengers, affecting ecosystem structure and function (Allen et al 2014; O’Bryan et al 2019) In south-eastern Spain, red foxes ( Vulpes vulpes ) were observed to be in higher abundance in areas where the absence of vultures ( Gyps spp.) increased carrion availability (Morales-Reyes et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Scavenging is an essential ecological function for maintaining stability in the ecosystem, via the control of community composition and carrion availability (Wilson & Wolkovich 2011; Barton et al 2013; Buechley & Şekercioğlu 2016). As most carnivores are facultative scavengers, their loss can influence herbivore density and prompt mesopredator release (O’Bryan et al 2019). For example, in north-east Tasmania, where Tasmanian devils ( Sarcophilus harrisii ) have declined due to devil-facial-tumour disease, feral cats ( Felis catus ) and forest ravens ( Corvus tasmanicus ) have increased in abundance due to increased access to carrion (Cunningham et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Altered distributions may induce shifts within species communities and in predator–prey dynamics (Krebs & Elwood, 2008; Tylianakis, Didham, Bascompte, & Wardle, 2008), potentially leading to cascading effects (Ripple & Beschta, 2012). A well‐known ecological cascade is extirpation of apex predators causing increased mesopredator abundance with subsequent decline in the abundance of prey species (O'Bryan, Holden, & Watson, 2019; Prugh et al., 2009).…”
Section: Introductionmentioning
confidence: 99%